Microbiological Analysis of the Urine Isolates in Kathmandu Medical College Teaching Hospital, Kathmandu, Nepal - Raza, S; Pandey, S; Bhatt, C P (Kathmandu University Medical Journal, 2012)
Background Urinary tract infections (UTIs) are the common cause of bacterial infection. Recently UTI become more complicated and difficult to treat because of appearance of pathogen with increasing resistance to antimicrobial agents. Objective To determine the etiology of the urinary tract infections and their susceptibility to antimicrobial agents. Methods This study was carried out in Kathmandu Medical College, at department of microbiology. Total 3,460 urine samples were tested microbiologically by standard procedure. Antibiotic susceptibility test was performed for all the isolates by Kirby Bauer disc diffusion method and result was interpreted according to National Committee for Clinical Laboratory Standards (NCCLS) guide line. Results Out of 3,460 urine samples 680 (19.7%) showed the significant bacteriuria. The most common pathogens isolated were Escherichia coli 75.7% followed by Klebsiella pneumoniae 10.7%, Acinetobacter spp 5.5%, Proteus spp 3.5% and Pseudomonas aeruginosa 1.2%. Most susceptible antibiotic was Amikacin, Ceftriaxone and Ciprofloxacin for most of the isolates. E. coli which was the main isolate was found to be most susceptible to Amikacin 96.1%, Nitrofurantoin 91.3% and Gentamicin 77.7% followed by Ceftriaxone 65.8% and Ciprofloxacin 64.1%. Conclusion Regular surveillance of the resistance rate among uro-pathogens is needed to ensure the appropriate therapy of UTI. DOI: http://dx.doi.org/10.3126/kumj.v9i4.6348 Kathmandu Univ Med J 2011;9(4):295-7